Association Between Continuous Performance and Response Inhibition Tests in Adults With ADHD. Issue 3 (February 2018) - Maoz, Hagai; Aviram, Shai; Nitzan, Uri; Segev, Aviv; Bloch, Yuval
Objective: The study of ADHD uses various computerized tests to assess cognitive functions. Uncertainty exists regarding the association between deficits found by different tools testing similar or different cognitive functions (e.g., continuous performance tests [CPT] and response inhibition [RI] tests).We hypothesized that different tools that measure continuous performance will be better correlated between themselves than with a tool that examines RI.Method: Thirty-six adults with ADHD performed two different CPTs and a RI task. We analyzed correlations between different measures examined by the tasks.Results: There were strong correlations between corresponding measures in the CPTs. Correlations between the results in CPT and the RI task were only minimal.Conclusion: These findings support the specificity of impairments in different cognitive domains (continuous attention vs. RI) beyond the specific test used in the study of ADHD. Also, these findings strengthen the importance of specific discriminative cognitive domains in ADHD.